2011
DOI: 10.1016/j.bbrc.2011.02.079
|View full text |Cite
|
Sign up to set email alerts
|

The thioredoxin TRX-1 regulates adult lifespan extension induced by dietary restriction in Caenorhabditis elegans

Abstract: Dietary restriction (DR) is the only environmental intervention known to extend adult lifespan in a wide variety of animal models. However, the genetic and cellular events that mediate the anti-aging programs induced by DR remain elusive. Here, we used the nematode Caenorhabditis elegans to provide the first in vivo evidence that a thioredoxin (TRX-1) regulates adult lifespan extension induced by DR. We found that deletion of the gene trx-1 completely suppressed the lifespan extension caused by mutation of eat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 212 publications
(294 reference statements)
0
29
0
Order By: Relevance
“…Loss of trx-1 completely suppresses the extended lifespan caused by mutation of eat-2, a genetic surrogate of DR in the worm (Fierro-Gonzalez et al, 2011). Interestingly, loss of trx-1 almost completely suppresses the lifespan extension produced by dietary deprivation (DD), a non-genetic model of DR in the worm (Fierro-Gonzalez et al, 2011). Thioredoxins comprise a conserved family of proteins that mostly depend on their oxidoreductase activity to reduce disulfide bonds in many target proteins .…”
Section: Metabolic Protein Deacetylation: the Sirtuin Familymentioning
confidence: 98%
See 1 more Smart Citation
“…Loss of trx-1 completely suppresses the extended lifespan caused by mutation of eat-2, a genetic surrogate of DR in the worm (Fierro-Gonzalez et al, 2011). Interestingly, loss of trx-1 almost completely suppresses the lifespan extension produced by dietary deprivation (DD), a non-genetic model of DR in the worm (Fierro-Gonzalez et al, 2011). Thioredoxins comprise a conserved family of proteins that mostly depend on their oxidoreductase activity to reduce disulfide bonds in many target proteins .…”
Section: Metabolic Protein Deacetylation: the Sirtuin Familymentioning
confidence: 98%
“…Furthermore, thioredoxins have also been implicated in the regulation of aging. The first in vivo studies reporting the effects of mammalian Trx1 during aging showed that overexpression of human Trx1 in mice extends lifespan (Fierro-Gonzalez et al, 2011). Differently from histone acetyltransferases (HATs) which counterbalance histone deacetylases (HDACs), a counter-regulatory program to counterbalance sirtuin deacetylase function is less well established.…”
Section: Metabolic Protein Deacetylation: the Sirtuin Familymentioning
confidence: 99%
“…An important factor regarding the effects of CR could also be thioredoxin, as it is shown to be essential for the lifespan extension in C. elegans under dietary deprivation and knockouts of eat-2, a genetic surrogate of nematodal CR (Fierro-Gonzalez et al 2011). The oxidoreductase thioredoxin is not only involved in antioxidant response and redox regulation, but also acts as electron donor for metabolic enzymes and prevents aggregation of cytosolic proteins in the cell Holmgren 2007, Berndt et al 2008).…”
Section: Mitochondrial Hormesis and Lifespanmentioning
confidence: 99%
“…However, only limited information is present about their function and characteristics. 12,[62][63][64][65][66][67] Thioredoxins are highly specialized in their tissue, cell and compartmental expression pattern (Fig. 1).…”
Section: The Crucial Role Of Pdi's and Ero-1 To Maintain Er Homeostasmentioning
confidence: 99%
“…67 Besides their function in redox homeostasis, thioredoxins have also been described to be involved in dauer formation, life span regulation and innate immunity. 63,66,67,70 The J-protein DNJ-27 combines chaperone function with classical TRX and PDI active sites A prominent member of the thioredoxin family that combines protein and redox homeostasis functions in one protein is the J-protein DNJ-27, which is the homolog of the mammalian ERdj5. 64 Like its mammalian homolog, DNJ-27 harbors a N-terminal J-domain, 4 trx-like domains with the CXXC motif (CSHC, CPPC, trx motif CGPC, PDI motif CGHC) and 2 divergent trx-like domains without CXXC motif (Fig.…”
Section: The Crucial Role Of Pdi's and Ero-1 To Maintain Er Homeostasmentioning
confidence: 99%